2019
DOI: 10.1186/s12879-019-3731-y
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and molecular characterization of the re-emerging measles virus among children and adults in the Haut-Ogooue, Gabon

Abstract: BackgroundMeasles is one of the most infectious diseases with a high mortality rate worldwide. It is caused by the measles virus (MeV) which is a single stranded RNA virus with genetic diversity based on the nucleoprotein gene, including 24 genotypes. In Gabon, several outbreaks occurred in the past few years, especially in 2016 in Libreville and Oyem. A surveillance network of infectious diseases highlighted a measles outbreak which occurred in the south of Gabon from April to June 2017.MethodsClinical specim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…Our phylogenetic analyses supported evidence from one previous study [ 17 ] that there is exclusive circulation of the B3 measles genotype in Senegal, as in several other sub-Saharan African [ 39 , 40 ], European [ 7 , 31 , 41 , 42 ] and Asian [ 32 ] countries. This differs to some settings in Europe, including France Italy and Romania where co-circulation of genotypes D8 and B3 have been detected [ 7 , 43 , 44 ].…”
Section: Discussionsupporting
confidence: 88%
“…Our phylogenetic analyses supported evidence from one previous study [ 17 ] that there is exclusive circulation of the B3 measles genotype in Senegal, as in several other sub-Saharan African [ 39 , 40 ], European [ 7 , 31 , 41 , 42 ] and Asian [ 32 ] countries. This differs to some settings in Europe, including France Italy and Romania where co-circulation of genotypes D8 and B3 have been detected [ 7 , 43 , 44 ].…”
Section: Discussionsupporting
confidence: 88%
“…1 This is due to the nature of this disease transmission by respiratory droplets or airborne spray. [4][5][6]24 Our study revealed that the cases had contact history with another confirmed case at home, school, or other public spaces. This finding is consistent with other studies where individuals who had a contact history with measles cases had a higher risk of acquiring infection compared to those had no contact during outbreak.…”
Section: Discussionmentioning
confidence: 70%
“…This finding is inline with other studies that revealed that measles cases related to non-vaccination status. 5,6,[22][23][24][25][26] Measles vaccination increases the immunity against measles [1][2][3][4] and high vaccination coverage reduces the risk of measles infection in the community. 24,27,28 Provision of measles vaccine is included in the Complete Routine Immunization Program recommended by the MoH of Indonesia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Briefly, RNA samples were prepared from clinical specimens, including throat swabs and stool and blister swabs using a QIAamp Viral RNA Mini Kit (Qiagen, Hilden, Germany). To confirm enterovirus infections, a one-step real-time reverse transcription polymerase chain reaction (RT-PCR) with primers and hydrolysis probes targeting the conserved region of 5′-UTR was performed [ 22 , 23 ]. The PCR assay modification was as follows: qScript XLT one-step rt-qpcr toughmix (Quantabio, MA, USA) was used as the master mix, and each reaction had ten pmol each of forward EQ1 (5′-ACATGGTGTGAAGAGTCTATTGAGCT-3′) and reverse primers EQ2 (5′-CCAAAGTAGTCGGTTCCGC-3′) and 2.5 pmol of probe EPmod (5′-ATTAGCCGCATTCAGGGGCCGGA-3′).…”
Section: Methodsmentioning
confidence: 99%